(untitled) (Journal of The Colloquium for Information Systems Security Education, 2026)
Cyberattacks on critical infrastructures motivate a focus on cybersecurity awareness. A knowledge gap exists in the technical and non-technical understanding of cybersecurity, in the workforce. Closing this gap requires a multi-faceted approach –of extreme importance is education. We use the NICE Workforce Framework TKS statements to develop a model of the most generalizable requirements needed to practice cybersecurity. We apply this model to increase cybersecurity language use and comprehension in all K-12 subjects, walking educators through a process incorporating cybersecurity into their lessons.